Hospital Volume of Thoracoabdominal Aneurysm Repair Does Not Affect Mortality in California. (July 2014) - Weiss, Anna; Anderson, Jamie A.; Green, Amanda; Chang, David C.; Kansal, Nikhil
Objectives: Open thoracoabdominal aneurysm repair (TAAR) is a rarely performed but a complicated and morbid procedure. This study compares the morbidity and mortality of open TAAR at high- versus low-volume hospitals. Methods: Included patients from California Office of Statewide Health Policy and Development patient discharge database who underwent an open TAAR between 1995 and 2010. High volume was ≥9 cases per year. Outcomes included mortality and postoperative complications. Multivariate analyses compared patients at high- versus low-volume hospitals. Results: A total of 122 hospitals were included, with 5 designated as high volume. Adjusted analysis found no difference in the odds ratio (OR) of mortality or morbidity at high-volume hospitals compared to low-volume hospitals (OR 0.37, P = .077; OR 0.94, P = .834, respectively). However, there was a decreased OR of mortality in high- versus low-volume hospitals when a high-volume hospital was defined as each year after meeting the initial threshold of 9 cases (OR 0.40, P = .040). Conclusion: We found no difference in mortality between low- and high-volume institutions in California, until high-volume hospitals were defined as each year after meeting initial threshold case volume. This may suggest that the benefits of high-volume hospitals on outcomes are maintained after reaching the requisite case volume.